2013
DOI: 10.1039/c3cc42296h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of renewable diesel with hydroxyacetone and 2-methyl-furan

Abstract: Synthesis of renewable diesel with hydroxyacetone and 2-methyl-furanDiesel or jet fuel range branched alkanes were synthesized for the fi rst time by the combination of hydroxyalkylation-alkylation (HAA) of 2-methylfuran with hydroxyacetone and hydrodeoxygenation. Compared with the previous acetone route, hydroxyacetone route exhibited higher HAA reactivity and diesel yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 25 publications
2
76
0
1
Order By: Relevance
“…Then, the glucoses must be further dehydrated or isomerized to a wide spectrum of platform chemicals, 8,[13][14][15][16] among which 2-methylfuran (2MF) and butanal have recently attracted interests. [17][18][19] Recent research by Corma et al has demonstrated a promising multi-step technique for producing long-chain hydrocarbons from 2-methylfuran (2MF) and butanal with high activity. 20 First, Amberlyst-15 is used as an acid catalyst in a liquid-phase batch reaction to hydroalkylate 2MF with butanal into 1,1-bisylvylalkanes, which are then separated from 2MF, butanal and water (side product).…”
Section: -3mentioning
confidence: 99%
“…Then, the glucoses must be further dehydrated or isomerized to a wide spectrum of platform chemicals, 8,[13][14][15][16] among which 2-methylfuran (2MF) and butanal have recently attracted interests. [17][18][19] Recent research by Corma et al has demonstrated a promising multi-step technique for producing long-chain hydrocarbons from 2-methylfuran (2MF) and butanal with high activity. 20 First, Amberlyst-15 is used as an acid catalyst in a liquid-phase batch reaction to hydroalkylate 2MF with butanal into 1,1-bisylvylalkanes, which are then separated from 2MF, butanal and water (side product).…”
Section: -3mentioning
confidence: 99%
“…Among these base catalysts, KOH showed superior performance in this process by obtaining the highest condensation product yield of 56%. Meanwhile, using Na 2 CO 3 , Ca(OH) 2 and Ba(OH) 2 as the catalysts, both of the EL and FA conversion, and the yield of condensation product yield were significantly reduced. The sequence of activities for the base catalysts decreased in the order of KOH>NaOH>LiOH>Ca(OH) 2 >Ba(OH) 2 >Na 2 CO 3 .…”
Section: Synthesis Of Renewable Jet Fuel Precursors From C-c Bond Conmentioning
confidence: 98%
“…Materials FA (≥99.5%, analytical reagent) was purchased from Tianjin Damao Chemical Reagents Factory. EL (≥99.5%, analytical reagent) and 5%Pd/C catalysts were purchased from Aladdin industrial Co. Ltd. Methanol (≥99.5%, analytical reagent) was purchased from Tianjin Fuyu Fine Chemical Co. Ltd. KOH, NaOH, LiOH, Ba(OH) 2 , Ca(OH) 2 and Na 2 CO 3 were purchased from Tianjin Fuchen Chemical Reagents Factory. All of these materials were used as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Aldol condensations of FF/HMF and/or their derivatives with carbonyl groups like acetone, [12][13][14][15][16] hydroxyacetone, 17 butaldehyde, 18 2-butanone, 19 methyl isobutyl ketone, 20 levulinic acid 11,21,22 and angelica lactone 23 have commonly been conducted to obtain the C 9 -C 16 fuel precursors, but these carbonyl compounds originate from fossil resources or are produced from biomass by multi-step reactions, leading to low efficiency and high cost for the entire synthesis. As an alternative, hydroxyalkylation-alkylation of FF and 2-methylfuran obtained by hydrodeoxygenation of FF was reported to produce C 15 fuel precursors with a branched carbon framework.…”
Section: -4mentioning
confidence: 99%